3D web freestanding RuO2–Co3O4 nanowires on Ni foam as highly efficient cathode catalysts for Li–O2 batteries. Issue 41 (27th June 2018) - Jiang, Zhuo-Liang; Xie, Jing; Luo, Cong-Shan; Gao, Meng-Yang; Guo, Huan-Liang; Wei, Mo-Han; Zhou, Hong-Jun; Sun, Hui
Abstract : Freestanding RuO2 –Co3 O4 nanowires on Ni foam were synthesized and applied as a cathode in Li–O2 battery. This cathode can deliver a high capacity of 9620 mA h g −1 and stable long-term operation exceeding 122 cycles at 100 mA g −1 . Abstract : The mechanism of Li–O2 batteries is based on the reactions of lithium ions and oxygen, which hold a theoretical higher energy density of approximately 3500 W h kg −1 . In order to improve the practical specific capacity and cycling performance of Li–O2 batteries, a catalytically active mechanically robust air cathode is required. In this work, we synthesized a freestanding catalytic cathode with RuO2 decorated 3D web Co3 O4 nanowires on nickel foam. When the specific capacity was limited at 500 mA h g −1, the RuO2 –Co3 O4 /NiF had a stable cycling life of up to 122 times. The outstanding performance can be primarily attributed to the robust freestanding Co3 O4 nanowires with RuO2 loading. The unique 3D web nanowire structure provides a large surface for Li2 O2 growth and RuO2 nanoparticle loading, and the RuO2 nanoparticles help to promote the round trip deposition and decomposition of Li2 O2, therefore enhancing the cycling behavior. This result indicates the superiority of RuO2 –Co3 O4 /NiF as a freestanding highly efficient catalytic cathode for Li–O2 batteries.